2020
DOI: 10.1002/lary.29038
|View full text |Cite
|
Sign up to set email alerts
|

Pain After Ear Surgery: A Prospective Evaluation of Endoscopic and Microscopic Approaches

Abstract: Objectives/Hypothesis Assumed advantages of a minimally invasive endoscopic transmeatal approach in ear surgery are less postoperative pain, faster healing, and preservation of functional anatomy. We evaluated pain after ear surgery and compared endoscopic transmeatal, microscopic endaural, and retroauricular approaches. Study Design Prospective cohort study. Methods A prospective evaluation of pain during 3 weeks after ear surgery was performed. Three groups were defined: endoscopic transmeatal, microscopic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 33 publications
(37 reference statements)
1
8
1
1
Order By: Relevance
“…5 Baazil et al reported that the endaural microscopic group required half as much medication as their retro-auricular microscopic and endaural transmeatal groups, a result which is unexplained. 6 However, their endoscopic group had a lower requirement for opioids for pain control post-operatively compared to the other groups, consistent with our findings. We therefore believe that the current evidence points towards lesser analgesia requirements after EES.…”
Section: Analgesia Requirementssupporting
confidence: 89%
See 3 more Smart Citations
“…5 Baazil et al reported that the endaural microscopic group required half as much medication as their retro-auricular microscopic and endaural transmeatal groups, a result which is unexplained. 6 However, their endoscopic group had a lower requirement for opioids for pain control post-operatively compared to the other groups, consistent with our findings. We therefore believe that the current evidence points towards lesser analgesia requirements after EES.…”
Section: Analgesia Requirementssupporting
confidence: 89%
“…Of note, operations studied by Baazil et al, within the endoscopic group included tympanoplasty and atticotomy; and those within the microscopic groups included stapedotomy, tympanoplasty, atticotomy, and canal wall up mastoidectomies. 6 Our study included stapes procedures only within the endoscopic group, and canal wall down mastoidectomy within the microscopic group (Table 1), perhaps explaining our relatively higher pain scores in the microscopic group.…”
Section: Summary Of Results/comparison With Literaturementioning
confidence: 98%
See 2 more Smart Citations
“…Mögliche Vorteile könnten v. a. in einer geringeren postoperativen Schmerzentwicklung bestehen. In einer Studie an insgesamt 60 Patienten mit jeweils transmeatal endoskopischer, endauraler Inzision und retroaurikulärem Zugang konnten allerdings keine signifikanten Unterschiede bezüglich dieser Vermutung aufgezeigt werden [ 4 ]. Insgesamt kann nach der vorliegenden Umfrage festgestellt werden, dass der chirurgische Zugangsweg in den EES-Kliniken in Deutschland sehr unterschiedlich gehandhabt wird.…”
Section: Diskussionunclassified